Dinamika Pendidikan Islam: Studi Perubahan Kelembagaan dan Metodologi Pada Madrasah Model - Taufik Churahman; Musfiqon Musfiqon (Universitas Islam Negeri Mataram, 2008)
In this article, I study Islamic education developing in undulated ways from the classic to modern era, including in Indonesia. There is dynamics in two cases: institution and methodology. In term of institutional dynamics, Islamic educational institutions are established through three phases: mosques, Khan Mosques and madrasahs. In Indonesia, madrasahs are formed from teaching and learning in Muslim leaders’ (kiyais) houses, mosques, Islamic boarding schools (pesantren) and then madrasahs. In term of methodological dynamics, Islamic education in madrasahs is started from lecture, memorization, and open discussion. In Indonesia, the developed methods are lecture given through sorogan, bandongan, and classical ways. Those institutional and methodological dynamics bring about madrasahs have special characteristics as particular Islamic educational institutions. As a result, excellent and model madrasahs have been established recently.